Development of Competitive Natural Gas Markets in the United States - Juris, Andrej (World Bank, Washington, DC, 2012)
The United States has the world's largest natural gas market. Fifteen years of deregulation have delivered significant gains to consumers in the form of lower prices and more services. The experience shows that liberalizing wholesale gas prices and the bulk supply of natural gas frees market forces in segments where competition is feasible. But regulators must focus on improving the regulation of pipeline transportation and minimizing its distortive effect on competitive gas markets. Introducing flexibility into pricing and other conditions of transportaion contracts such as delivery locations or the balancing of gas shipments and standardizing pipeline operations promote more efficient use of pipelines and benefit all industry participants. The U.S. experience also shows the important role of gas marketers and spot markets in increasing the efficiency of gas transactions and prices. Deregulation of the U.S. gas industry is far from complete, however. The most important task, and the biggest challenge for regulators, remains the deregulation of retail gas markets in individual states.